Popular Music Media Literacy: Recommendations for the Education Curriculum. (October 2019) - Wright, Chrysalis L.; Dillman Carpentier, Francesca; Ey, Lesley-Ann; Hall, Cougar; Hopper, K. Megan; Warburton, Wayne
Advances in technology have made music more readily accessible and geographic distance irrelevant in dissemination of music. Greater access to popular music has resulted in greater consumption by both children and adolescents. Popular music in the United States may contain the most sexual content, compared with other forms of media. Exposure to such content is associated with the development of gender ideals and identity, objectification and sexualization of women, permissive sexual attitudes and risky sexual behaviors, as well as greater acceptance of sexual and gendered violence. Even so, current education standards do not include media literacy, much less popular music media literacy, and do not prepare children for best practices related to media consumption. Some of the inadequacies in current education standards include introducing education about media influence on personal development at an age far later than children's engagement with contemporary media, avoidance of controversial topics, and not making this education compulsory. Considering the lack of media literacy provided in the curriculum, we outline specific foundational curricular recommendations related to media education and specifically for popular music media literacy.